THEORETICAL BASIS OF TEACHING READING SKILLS (Journal of Science-Innovative Research in Uzbekistan, 2023)
Reading skills are abilities that pertain to a person's capacity to read, comprehend, interpret and decode written language and texts. Exceptional reading skills can be highly beneficial to assimilating and responding to written communications like emails, messages, letters and other written messages.